Nonlinear dynamic analysis and feedback control of thermoacoustic instability - Li, Xinyan (2018)
This dissertation mainly studies the nonlinear dynamic behaviors of thermoacoustic instability and feedback control of thermoacoustic oscillations numerically and experimentally. Rijke-type thermoacoustic systems are modeled for numerical investigation, and experimental investigations are conducted on a Rijke tube. Coupling the heat input with Galerkin series expansion of flow disturbances provides a platform to gain insights on the time evolution of system's response.